Genomic analysis of Listeria monocytogenes strains from dairy products in Ethiopia - Mebrie Zemene Kinde; Bizuayehu Kerisew; Tegegne Eshetu; Abebe Tesfaye Gessese (Frontiers in Bioinformatics)
This study explored virulence genes, antibiotic resistance genes, and mobile genetic elements in 14 Listeria monocytogenes strains from milk and dairy products collected from different regions of Ethiopia. The strains were classified into two Multilocus Sequence Typing sequence types (ST2 and ST45) and further grouped into clonal complexes (CC2) and different cgMLST types. Twenty-nine virulence genes were identified across all 14 strains, with lplA1 detected at higher levels in all strains except SAMN28661660. All L. monocytogenes strains also carried four antibiotic resistance genes (fosX, lin, norB, mprF), contributing to their ability to withstand multiple antimicrobial agents. Notably, no plasmids or mobile genetic elements were detected. Stress resistance genes, including stress survival islet 1 (SSI1_lmo0447), lmo 1800, and lmo1799, were identified in all strains. However, genes encoding for disinfectant resistance were not identified from all strains. LGI-2 was found in all the strains and none of the studied strains harbored LGI-1 and LGI-3. Conserved CRISPR-Cas systems were found in some strains. KEGG pathway analysis revealed that inlA and inlB genes facilitate bacterial internalization through host actin polymerization. Overall, the study provided crucial insights into the genomic features of L. monocytogenes in the Ethiopian dairy chain. It is crucial to establish continuous monitoring of L. monocytogenes in dairy products, improve sanitation, enforce stricter antibiotic usage and food safety regulations, and raise public awareness of associated risks.